Assessment Of Risk Factors For Irritable Bowel Syndrome - Makhmudova L.I; Eshniyazova G.Sh (Zien Journals, 2024)
Irritable bowel syndrome (IBS) is a biopsyosociological disease that is not associated with organic intestinal changes. In total, 82 patients were investigated and 20 healthy contingent. Patients were made into two groups: the first group of patients with IBS that are divided into 2 small groups: IBSd (diarrhea) - 49 patients (26 men and 23 women) and IBSc (constipation) - 33 patients (15 men and 18 women). Abdominal pain was more often noted in patients with a clinical form of IBS with a predominance of diarrhea. Estimation of the severity of IBS symptoms allows to objectify the severity of clinical manifestation of intestinal dysfunction in patients, identify the clinical features of this pathology.
Keywords: irritable bowel syndrome; clinical symptoms; psychological state